Konsep Keadilan Gender dalam Perspektif Al-Qur’an: Studi Tafsir Tematik (Maudhu’i) - Zebada Darell Frijatuluah (Dirosah Islamiyah, 2026)
Gender justice is one of the central issues in contemporary Islamic discourse and often becomes a subject of debate between normative religious teachings and social practices. The Qur’an, as the primary source of Islamic teachings, contains universal principles of justice, including those related to gender relations. This study aims to examine the concept of gender justice from the Qur’anic perspective using a thematic interpretation (maudhu’i) approach. This research employs a qualitative method with a library research design. The data are derived from Qur’anic verses related to gender relations, classical and contemporary Qur’anic commentaries, as well as relevant scholarly literature. Data analysis is conducted through the identification, classification, and thematic interpretation of the selected verses. The findings indicate that the Qur’an emphasizes gender justice through principles of spiritual equality, balance of social roles, and fairness in rights and responsibilities. Differences in roles between men and women are not intended as forms of discrimination but rather as a distribution of responsibilities based on justice. Therefore, the Qur’anic concept of gender justice remains relevant as a foundational framework for fostering just and harmonious gender relations in contemporary Muslim societies.